MANTRA: an ultra lightweight cipher design for ubiquitous computing. (2018) - Bansod, Gaurav; Pisharoty, Narayan; Patil, Abhijit
In this paper, we are proposing an ultra lightweight cipher MANTRA. MANTRA is a Feistel-based network which operates on 64-bit plain text and supports 128/80-bit key length. It needs very less footprint area and consumes only 1662 gate equivalents for the 128-bit key length and 1374 for 80-bit key length. The novel design of MANTRA uses a Feistel within a Feistel structure. Its memory size is less as compared to existing lightweight ciphers. In this paper, we have presented the security analysis of MANTRA and its performance as an ultra lightweight cipher. A strong permutation layer in MANTRA prevents clustering of linear and differential trails when the cipher is attacked. MANTRA shows good resistance against Biclique and zero correlation attacks. MANTRA is a cipher design well suited for the applications where small footprint area and low power dissipation play crucial role.